Accessibility of the Urban Greenery System as a Component of the Quality-of-Life Assessment in Cities - Sara BRĘCZ-KUPIEC; Michał KUPIEC (Communications of International Proceedings, 2021)
The issue of accessibility of green infrastructure in city areas is the subject of numerous interdisciplinary studies. They combine methods using spatial analysis, sociological research and strong economic and spatial planning threads. The article presents an overview of the concept and results of accessibility research. The list of research trends presented shows a great variety of approaches as well as discrepancies in results and assessments, which depend to such a large extent on the adopted assumptions, and in particular simplifications in the research methodology. The analyzed studies take into account various approaches to defining the extents of the concept of urban greenery, various geometric methods for defining greenery accessibility zones, the issue of time as a variable in accessibility analyzes and the analysis of the impact of accessibility on the economic indicators of urban space and their impact on the mental and physical health of residents.
Keywords: Urban green areas; accessibility; quality of life